Prospect into therapeutic potentials of Moringa oleifera phytocompounds against cancer upsurge: de novo synthesis of test compounds, molecular docking, and ADMET studies - Aja, P. M.; Agu, P. C.; Ezeh, E. M.; Awoke, J. N.; Ogwoni, H. A.; Deusdedit, Tusubira; Ekpono, E. U.; Igwenyi, I. O.; Alum, E. U.; Ugwuja, E. I.; Ibiam, A. U.; Afiukwa, C. A.; et al. (Bulletin of the National Research Centre, 2021)
Background: Cancer chemotherapy is difficult because current medications for the treatment of cancer have been linked to a slew of side effects; as a result, researchers are tasked with developing greener cancer chemotherapies. Moringa oleifera has been reported with several bioactive compounds which confirm its application for various ailments by traditional practitioners. In this study, we aim to prospect the therapeutic potentials of M. oleifera phytocompounds against cancer proliferation as a step towards drug discovery using a computational approach. Target proteins: dihydrofolate reductase (DHFR) and B-Cell Lymphoid-2 (BCL-2), were retrieved from the RCSB PDB web server. Sixteen and five phytocompounds previously reported in M. oleifera leaves (ML) and seeds (MS), respectively, by gas chromatography–mass spectrometry was synthesized and used in the molecular docking study. For accurate prediction of binding sites of the target proteins; standard inhibitors, Methotrexate (MTX) for DHFR, and Venetoclax (VTC) for BCL-2, were docked together with the test compounds. We further predicted the ADMET profile of the potential inhibitors for an insight into their chance of success as candidates in drug discovery. Results: Results for the binding affinities, docking poses, and the interactions showed that ML2, ML4-6, ML8-15, and MS1-5 are potential inhibitors of DHFR and BCL-2, respectively. In the ADMET profile, ML2 and ML4 showed the best drug-likeness by non-violation of Lipski Rule of Five. ML4-6, ML8, ML11, ML14-15, and MS1, MS3-5 exhibit high GI absorption; ML2, ML4-6, ML8, MS1, and MS5 are blood–brain barrier permeants. ML2, ML4, ML9, ML13, and MS2 do not interfere with any of the CYP450 isoforms. The toxicity profile showed that all the potential inhibitors are noncarcinogenic and non-hERG I (human ether-a-go-go related gene I) inhibitors. ML4, ML11, and MS4 are hepatotoxic and ML7, ML10, and MS4 are hERG II inhibitors. A plethora of insights on the toxic endpoints and lethal concentration values showed that ML5, ML13, and MS2 are comparatively less lethal than other potential inhibitors. Conclusion: This study has demonstrated that M. oleifera phytocompounds are potential inhibitors of the disease proteins involved in cancer proliferation, thus, an invaluable step toward the discovery of cancer chemotherapy with lesser limitations.
Keywords: Cancer upsurge; Moringa oleifera phytocompounds; Molecular docking; De novo synthesis; ADMET profile; Potential inhibitors